The Development of accounting System and Accounting Education in High Income Oil Exporting Countries: An Overview - Yapa, Senarath; Wijewardena, Hema (Accounting Department,, 1996)
For a considerable length of time, the development in Third World countries (TWCs) identified by many wirters on the basis of viewing these countries as a single economic grup. As a result of the rapid economic changes taken place after the oil boom the development of accounting systems and accounting education in high income oil exporting countries (HIOECs) has been significantly different from that of other TWCs. Therefore, the unified view of Third World accounting is no longer appropriate and the economic differentiation needs to be taken into account in any realistic classification of accounting in this part of the word. Further, the ‘sphere of influence’ methodology used by Enthoven (1977) for classifying accounting system in the Third World is not applicable to HIOECs because, unlike in other TWCs, the development of accounting and education in this particular group of countries is not an outcome of such historical factor as colonial experience and/or colonial affinity.